2014
DOI: 10.1111/tbed.12239
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Resource Requirements to Staff a Response to a Medium to Large Outbreak of Foot and Mouth Disease in Australia

Abstract: A recent report to the Australian Government identified concerns relating to Australia's capacity to respond to a medium to large outbreak of FMD. To assess the resources required, the AusSpread disease simulation model was used to develop a plausible outbreak scenario that included 62 infected premises in five different states at the time of detection, 28 days after the disease entered the first property in Victoria. Movements of infected animals and/or contaminated product/equipment led to smaller outbreaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
5
20
1
Order By: Relevance
“…The results of our estimations seem somewhat lower than what was estimated in Australia (17). Direct comparisons are difficult, due to geographical differences, resulting in several state disease control centers and local disease control centers in Australia, differences in estimated size of the epidemic, i.e., Garner et al chose a 90th percentile epidemic and differences in how results are presented.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of our estimations seem somewhat lower than what was estimated in Australia (17). Direct comparisons are difficult, due to geographical differences, resulting in several state disease control centers and local disease control centers in Australia, differences in estimated size of the epidemic, i.e., Garner et al chose a 90th percentile epidemic and differences in how results are presented.…”
Section: Discussioncontrasting
confidence: 99%
“…This was also in line with what was found by Garner et al (17). This means that if veterinarians doing surveillance visits can be more efficient, the number of needed veterinarians will decrease substantially.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These were applied according to each country’s FMD response plan (19, 26). Resources for disease control were based on each country’s estimates of expected resources (5). Each model run ended when disease was eradicated or after 1 year, whichever occurred first.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling studies carried out in Australia (3–5) and overseas (68) have shown that vaccination is effective in reducing the duration and/or size of FMD outbreaks in situations where disease is widespread, where there is a high rate of spread or the resources for stamping out are limited. Reports suggest that early vaccination may have been beneficial in eradicating the disease earlier than was the case with recent FMD outbreaks in Korea (9) and Japan (10).…”
Section: Introductionmentioning
confidence: 99%